What factors influence self-efficacy in teachers using mobile digital technology within the secondary school classroom? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Manawatu, New Zealand - Tilton, Josephine Anne (Massey University, 2014)
As digital technologies develop and change so do the way these tools are integrated into classrooms. In particular as mobile digital technologies develop further, there is a need to investigate how teachers engage with these both personally and in the classroom. Research has consistently indicated that a key element regarding the use and integration of digital technologies in the classroom are teachers’ underlying beliefs and attitudes, including self-‐efficacy theory. In this study, changes in and factors influencing mobile digital technology self-‐ efficacy are examined using a mixed methods research design. The study focused on the perspective of teachers in their first year of implementing a one-‐to-‐one iPad mini device programme within the context of an international school in Germany. Over the course of the implementation, all teachers reported some increase in the use of the iPad mini in the classroom, regardless of their own personal self-‐efficacy concerning the device. Findings included self-‐efficacy influences such as enactive experiences, modeling and coaching, with enactive experience being a foremost contributor to the development of teacher mobile technology self-‐efficacy. A sense of classroom collective efficacy was also a key finding. This sense of collective efficacy demonstrates a shared confidence between teacher and students in the classroom context regarding the use of the iPad mini devices. Device affordances in student organisation, differentiation (by difficulty and interest), and the encouragement of student agency were also evident as additional findings in the data, and contributed to the teachers’ perceived value of the iPad mini device.
Keywords: Mobile technology in education; Teachers' self-efficacy; Self-efficacy; Secondary education